PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DILUAR PENGADILAN MELALUI ARBITRASE - Jumadi Anwar; Imam Budi Santoso (SUPREMASI HUKUM, 2023)
Arbitration provides a procedure or process for resolving disputes peacefully and out of court. Arbitration opportunities for the sustainability of industrial relations in Indonesia are minimal things that will be implemented by all disputing parties because the community prioritizes settlement in terms of winning or losing through court settlements. It is very important that there are ways to support this arbitration as an option for resolving industrial disputes so that it is of interest to the public. The research method used in this study is a normative juridical research method with a descriptive approach, with the aim of providing direction and finding logical realistics by looking at library materials or other information using primary and secondary data. The results obtained from the conclusion of this discussion are the knowledge of the mechanism of arbitration in the settlement of disputes in the field of industrial relations and the advantages and disadvantages of arbitration in resolving problems in the field of industrial relations. Keywords: Arbitration, Industry, Disputes.